Effectiveness Evaluation of Smartphone Based Structure from Motion (SfM) Photogrammetry in Calculating the Volume of Regular Elements - Ahmad, Mohammad (Latakia University Journal -Engineering Sciences Series, 2025)
In this research, the effectiveness of the Structure from Motion (SfM) technique in calculating the volume of regular objects was verified by comparing the calculation results with the reference volume and the volume calculated using traditional topographic methods. In the proposed methodology, photos and video recordings were obtained using a smartphone and a digital camera. Then, 25 samples were formed by varying the parameters (geometric resolution, processing level, and number of photos) and repeating the calculation process. The models were then evaluated visually and geometrically. The results showed that when using high and medium processing levels with photos of high geometric resolution, the values were almost identical to those obtained from traditional methods, while differences increased with photos extracted from video recordings. Changing the number of photos did not affect the volume accuracy, as all values were close to each other. The overall accuracy of the photo triangulation ranged between 5mm and 24mm, with all values within acceptable limits. Additionally, the results indicated an increase in the number of points clouds and faces with higher resolution and a greater number of photos, with the difference values in relative comparison of point clouds ranging between 0mm and 9mm.